2018
DOI: 10.1155/2018/7453787
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Antiamoebic Activity of Methanol Extracts ofArgemone mexicanaon Trophozoites ofEntamoeba histolyticaHM1-IMSS

Abstract: Infections caused by parasites in humans represent one of the main public health concerns. Amoebiasis, a parasitic infection caused by Entamoeba histolytica (E. histolytica), is considered endemic in Mexico, where Argemone mexicana (A. mexicana) has been used in traditional medicine to treat intestinal parasitic diseases. The objective of this work was to evaluate the potential biological activity of A. mexicana on E. histolytica. For this purpose, a methanolic extract was prepared from A. mexicana leaves, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
11
0
4
Order By: Relevance
“…Antiparasitic activity of A. mexicana against different etiological agents has been demonstrated, as for example it has been found that it has effective activity against P. falciparum has also been demonstrated, as the aqueous extract of the aerial parts of this plant exhibited an IC50 of 5.9 μg/ml [24]. Activity of the methanolic extract of A. mexicana leaves against E. histolytica trophozoites has been reported, and the results revealed a dose-dependent behavior with lethality percentages of 98.1% and 75.0% at concentrations of 500 μg/ml and 125 μg/ml, respectively [25]. At the moment there are no reports of the use of extracts of A. mexicana or its fractions against T. vaginalis and our results seem even more promising when sub-fractions of the extracts [26] or the majority metabolite are evaluated, as in our case that Berberine showed a greater inhibitory capacity (IC50 = 40.7 μg/ml) compared to complete extracts analyzed by the Probit test, in which it can be seen that the upper and lower limits are overlapped between AmexS and AmexL, but not with berberine.…”
Section: Discussionmentioning
confidence: 88%
“…Antiparasitic activity of A. mexicana against different etiological agents has been demonstrated, as for example it has been found that it has effective activity against P. falciparum has also been demonstrated, as the aqueous extract of the aerial parts of this plant exhibited an IC50 of 5.9 μg/ml [24]. Activity of the methanolic extract of A. mexicana leaves against E. histolytica trophozoites has been reported, and the results revealed a dose-dependent behavior with lethality percentages of 98.1% and 75.0% at concentrations of 500 μg/ml and 125 μg/ml, respectively [25]. At the moment there are no reports of the use of extracts of A. mexicana or its fractions against T. vaginalis and our results seem even more promising when sub-fractions of the extracts [26] or the majority metabolite are evaluated, as in our case that Berberine showed a greater inhibitory capacity (IC50 = 40.7 μg/ml) compared to complete extracts analyzed by the Probit test, in which it can be seen that the upper and lower limits are overlapped between AmexS and AmexL, but not with berberine.…”
Section: Discussionmentioning
confidence: 88%
“…The control of schistosomiasis is based on praziquantel which has many deficiencies ( 22 ). Many investigations have evaluated several substances from plant origin, such as berberine, abundant in A. mexicana , shown promising properties against L. tropica , L. infantum , Trichomonas vaginalis, and E. histolytica ( 15 , 23 , 24 ). However, no studies have been conducted against S. mansoni .…”
Section: Discussionmentioning
confidence: 99%
“…After column chromatography (silica gel, Sephadex), this residue afforded the known flavonoids pinocembrin (1), sakuranetin (2), cirsimaritin (3), and naringenin (4), with significant antiamoebic activity (Figure 1). Currently, metronidazole is the most used commercial drug for the treatment of amoebiasis, however, since drug resistance by E. histolytica is increasing, the use of higher doses to overcome the infection is needed, thus causing unpleasant side effects [10,11]. Considering these undesired side effects as well as the development of resistant strains of E. histolytica against metronidazole, more efficient and safer antiamoebic agents are required [12][13][14].…”
Section: Bioguided Isolation Of Flavonoids From Lippia Graveolens Kunthmentioning
confidence: 99%